Ingestive behavior of beef cows submitted to different nutritional levels in the final third of pregnancy (Research, Society and Development, 2021)
The objective of this work was evaluate the ingestive behavior of beef cows submitted to different nutritional levels in the final third of gestation. Eighteen pregnant cows of the Charolais and Nellore breeds were used, divided into treatments: Low (exclusively on natural pasture); Medium (supplementation to meet maintenance requirements); High (supplementation to meet 150% of maintenance requirements). The randomized complete experimental design was used with six replicates per treatment and three evaluation periods. The time spent in other activities increased with pregnancy advancement and as the nutritional level in this period also increased, with values of 0.96; 1.86 and 3.24 hours day-1 for the Low, Medium and High treatments respectively. High treatment cows proved to be more selective, since they had less time per station (6.96 vs 9.18 and 10.19 seconds) and went through a higher number of stations per minute (9.51 vs 7.06 and 7 , 31) in relation to the Low and Medium cows, respectively. Shortest time per bite (1.45 seconds) and consequently a greater number of bite rate (41.86 bites/min) was obtained in the Low cows compared to Medium and High cows. Greater selectivity and grazing efficiency occurred at pregnancy end, with less displacement between stations (1.03 steps) and less time per station (6.42 seconds) resulting in a greater number of stations / minute (10.01 stations). Low-level cows are more efficient in apprehending pasture, while supplemented cows are more selective. As gestation advances, cows increase the selectivity of material ingested to meet greater metabolic demands associated with less consumption capacity.